A Review on Cloud Framework for Healthcare Analytics - Joshi, DL; Joshi, MA; Dande, AA; Wararkar, P (International Journal of Computer Sciences and Engineering, 2025)
With the wide spread use of the internet in almost all of the fields in our day to day life, has created many new opportunities and challenges in the Data Analytics. Data Analytics deals with the methods to processes, analyze and to draw the knowledge based conclusion from the data sets obtained from various sources applied to take proper decisions for any Artificial Intelligence based systems. Big Data Analytics deals with the larger sized data analytics in terabytes or peta bytes. Presently cloud computing along with Big Data Analytics has wide spread applications in many expert systems design. In this paper we are focused on the basic conceptual model used more specifically in Health Care Analytics using cloud framework based Big Data Analytics. Based on proper data sets available, this framework will be able to make proper healthcare analysis for preventive and remedial decisions.